Novel Survivin Peptides Screened With Computer Algorithm Induce Cytotoxic T Lymphocytes With Higher Cytotoxic Efficiency to Cancer Cells - Chen, Qiuqiang; Jia, Gang; Zhao, Xiaolei; Bao, Ying; Zhang, Yu; Ozkan, Cengiz; Minev, Boris; Ma, Wenxue (Frontiers in Molecular Biosciences, 2020)
The identification of novel biomarkers and therapeutic targets in advanced cancer is critical for improving cancer diagnosis and therapeutics. Survivin (SV) is highly expressed predominantly in most cancer cells and tissues but is absent or undetectable in terminally differentiated normal adult tissues. Therefore, it functions as an almost universal tumor antigen. Peptides are short chains of amino acids linked by peptide bonds. To obtain novel SV decamers that are able to induce SV-specific cytotoxic T lymphocytes (CTLs) with a higher cytotoxic efficiency against cancer cells, major histocompatibility complex (MHC) peptide binding algorithms were conducted to predict nine modified SV95 decamers (from SV95-2 to SV95-10) based on the natural SV95-104 peptide sequence of ELTLGEFLKL (here defined as SV95-1). The fluorescent density of each SV95 peptide was determined by a MHC stability assay, followed by the generation of SV95-specific CTLs with each SV95 peptide (from SV95-1 to SV95-10) and human dendritic cells (DCs) loaded with Poly(lactic-co-glycolic) acid (PLGA) nanoparticles encapsulated with SV95 peptide. Finally, IFN- ELISpot and CytoTox 96® Non-Radioactive Cytotoxicity Assays were employed to verify their cytotoxic efficiency of the SV95-specific CTLs generated with the corresponding artificial antigen presenting cells (aAPCs) containing SV95 (SV95-1 to SV95-10) peptide. Furthermore, the cytotoxicity of the SV95 specific CTLs generated with nine mutated SV95 peptides was compared to the one generated with natural SV95-1 peptide and TIL2080 cells. The results indicated that the HLA-A2-restricted mutated SV95 epitope decamers (SV95-6 and SV95-7) showed significant higher binding ability compared to natural peptide SV95-1 in MHC stability assay. More importantly, SV95-specific CTLs with higher cytotoxicity were successfully induced with both SV95-6 and SV95-7 peptides, which significantly eliminated target cells (not only SV95-1 peptide pulsed T2 cells, but also both HLA-A2 and SV positive cancer cells) when compared to those generated with natural SV95-1 peptide and TIL2080 cells. These findings suggest that the SV95-6 and SV95-7 peptides are two novel HLA-A2-restricted CTL epitopes and may be useful for the immunotherapy for patients with survivin expressing cancer.